The pastoral crowd: Exploring self‐hosted crowdfunding using activity theory and social capital. (8th May 2017) - Gleasure, Rob; Morgan, Lorraine
Abstract: As crowdfunding technologies mature, designers and practitioners are continuing to discover new paradigms for fund‐raising activities. One such paradigm seeks to complement or replace third‐party crowdfunding websites by embedding crowdfunding technologies directly into fund seekers' personal websites. This promises more control and customisation for fund seekers yet also distances fund‐seeking activities from the established crowds on websites such as Kickstarter and Indiegogo. Consequently, fund seekers adopting this paradigm must be capable of gathering and sustaining a suitable crowd that does not already exist in any one location. However, not all organisations are likely to possess the social resources to meet this challenge. Of those that do, little is known about how they might leverage these resources or the manner in which specific resources have an impact. Thus, the objective of this study is to explore the social resources that enable self‐hosted crowdfunding activities. In particular, this research models these activities by leveraging 2 a priori theoretical lenses: activity theory and social capital theory. These are applied to analyse an extreme case of self‐hosted crowdfunding, the funding of Star Citizen. Observations from this case are used to develop a propositional model that links different types of social capital with specific elements of self‐hosted crowdfunding.